Technical feasibility of line-assisted complete closure technique for large mucosal defects after colorectal endoscopic submucosal dissection - Kato, Minoru; Takeuchi, Yoji; Yamasaki, Yasushi; Arao, Masamichi; Suzuki, Sho; Iwatsubo, Taro; Hamada, Kenta; Tonai, Yusuke; Shichijo, Satoki; Matsuura, Noriko; Nakahira, Hiroko; Kanesaka, Takashi; Akasaka, Tomofumi; Hanaoka, Noboru; Higashino, Koji; Uedo, Noriya; Ishihara, Ryu; Iishi, Hiroyasu (Endoscopy International Open, 2017)
Background and study aims Complete closure of large mucosal defects after colorectal endoscopic submucosal dissection (C-ESD) is considered impossible in most cases because of the limited width of the open clip. We therefore invented a simple closure technique using clip-and-line, named “line-assisted complete closure (LACC)”, and assessed its technical feasibility.Patients and methods Between January and February 2016, we performed LACC in 11 patients after C-ESD and included them in this retrospective feasibility study. Outcome measures were procedural success rate, procedure time, and post-procedural complications.Results The median size of the resected specimen was 36 mm (range 30 – 72 mm). Procedural success was achieved in 10 of 11 cases (91 %). Those 10 cases required a median of 9 endoclips (range 6 – 12) for complete closure. Median procedure time for LACC was 14 minutes (range 6 – 22). No complications were observed in any of the cases after the procedure.Conclusion LACC is a simple and feasible technique for complete closure of large mucosal defects after C-ESD.